Building Customer Loyalty: The Role of Price Perception, Product Quality, and Packaging Quality - Afiffuddin, Muhammad Abyan; Hussein, Ananda Sabil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Customer loyalty is a crucial aspect in maintaining business sustainability, especially for agribusiness enterprises such as Karya Lestari Farm. This study aims to analyze the influence of price, product quality, and packaging quality on customer loyalty. The method used is explanatory research with a quantitative approach. The population of the study consists of consumers of Karya Lestari Farm, with a sample of 180 respondents obtained through purposive sampling. Data were collected through questionnaires and analyzed using instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing with the assistance of SPSS version 22 for Windows. The results show that all three variables, namely price, product quality, and packaging quality, have a significant and positive influence on customer loyalty. These findings affirm that these aspects are important determinants in building and maintaining consumer loyalty. The implication of this study encourages Karya Lestari Farm to focus on setting competitive prices, improving product quality, and creating attractive packaging designs to strengthen long term relationships with customers.